Signal accuracy and informational cascades - Ivan Pastine; Tuvana Pastine (University College Dublin, UCD School of Economics, 2006)
We extend the Bikhchandani, Hirshleifer and Welch (1992) informational cascade framework to allow for asymmetric signal accuracy. Simulations demonstrate that even small departures from symmetry may lead to non-monotonic effects of signal accuracy on the likelihood of an inefficient cascade.
hdl:10197/698
Keywords: D80; 330; Learning; Herding; Signal Precision